Mathematical model for ice wall interactions within a level set method. (2016) - Morency, François; Beaugendre, Héloïse
De-icing systems work periodically to remove ice formed on aircraft protected surfaces. They achieve this result by reducing adhesive shear strength between ice and surfaces. In the present work, an immersed boundary method will predict ice-shedding trajectories and collisions. At the starting-point of shedding trajectory calculations, when the ice-shed particle is still close to the wing surface, there is a high probability of collision with the surface. A linear spring collision model is presented assuming the interacting bodies are connected tangentially and normally by linear springs. The verification of the model is made by comparison with literature results and study of ice trajectories around a cylinder and an aerofoil.